Broccoli and Arthritis: A Review - Mingyuan Song; Xingquan Xu; Prachi Wele; Ding Wei; Xian Wu; Wenjin Yan (Food Frontiers)
ABSTRACT Arthritis is a disease characterized by joint pain, swelling, and limited mobility and is also a major cause of disability. Osteoarthritis (OA) and rheumatoid arthritis (RA) are the two most common manifestations of arthritis, and they share many common risk factors and pathogenic features. At present, there is no effective approach to prevent the disease or slow its progress. Nonetheless, many treatments can alleviate symptoms and improve the quality of life of patients. Among, antioxidant supplement therapy has become one of the most popular methods as it can inhibit the formation of reactive oxygen species (ROS) in chondrocytes, which is a key step in the pathogenesis of arthritis. Broccoli is rich in many essential nutrients, including fibers, vitamins, minerals, and various bioactive components. Thus, a dietary supplement of broccoli holds potential as a preventive measure against arthritis due to its widespread popularity, safety profile, and affordability. However, no review of the clinical and pre‐clinical studies of broccoli on arthritis is available so far. Therefore, this systematic review aims to critically evaluate the efficacy and safety of broccoli and its bioactive constituents in the treatment of arthritis. Although the current evidence falls short of establishing a definitive effect of broccoli on arthritis due to a limited number of clinical studies and significant heterogeneity among the existing research, current research provides overall support for the potential benefits of broccoli and its bioactive components in preventing and managing arthritis and the use of broccoli as an adjuvant treatment for individuals with arthritis.